Efektivitas dan Aspek Hukum Penguasaan Wilayah Perairan Danau Tempe Untuk Pemukiman Rumah Terapung Masyarakat Nelayan - Andi Bau Mallarangeng; Yustiana; Yusuf, Nurchaeriyansyah; Rina Febriyanti; Umar, Heriyadi (YP-SDI Lamaddukelleng, 2025)
This study aims to determine the status of control over the waters of Lake Tempe, which are used as fishermen's settlements in the form of floating houses in Wajo Regency, and the efforts made by the government to control the area. The research method uses two methods, namely normative legal research, by taking legal data sources and secondary data, by processing data from primary, secondary, and tertiary legal materials. Data collection tools include library research, and qualitative research with field research, through observation and interviews and documentation of respondents. The results of the study are that the status of control over the waters of Lake Tempe, which are used as fishermen's settlements in the form of floating houses in Wajo Regency, has not yet received written legitimacy from the government. Control by the community is only based on evidence of physical control passed down from generation to generation. This is the local wisdom of the community in Wajo Regency, that ready goods that actually control the waters for floating houses, then it is the ownership of each member of the community. And efforts made by the government to control the waters of Lake Tempe in the form of floating houses by fishermen in Wajo Regency until now have not existed. This is proven by the absence of regional regulations governing the allocation of these floating houses, even though these floating houses are the local wisdom of the people of Lake Tempe which must be preserved